REPRESENTATION OF INEQUALITY IN ACCESS TO EDUCATION: A CRITICAL DISCOURSE ANALYSIS OF THE NEWS OF "FORMER CHICKEN COOP BECOMES SCHOOL" (NORMAN FAIRCLOUGH'S APPROACH) - Siti Suwadah Rimang; Alfina, Aisyah Eka; D. Wulan Azzahra; Irmawati; Liasmin (Multidisciplinary Indonesian Center Journal (MICJO), 2025)
This study aims to analyze and identify how the news of "Former Chicken Cage Becomes School" represents the inequality of access to education with the framework of Norman Fairclough's critical discourse analysis. This study adopts a descriptive qualitative method using Norman Fairclough's critical discourse analysis (AWK) as the main framework. Data is collected through documentation and recording of news texts from relevant online media. Data analysis was carried out sequentially covering Fairclough's three dimensions: microstructural analysis (word choice, sentence structure, rhetorical strategy), mesostructural analysis (the practice of production and distribution of news texts), and macrostructural analysis (social and ideological relationships that underlie discourse). The results of this study reveal the complex representation of inequality in access to education through critical discourse analysis (AWK) on the news "Former Chicken Cage Becomes School" with the Norman Fairclough approach. Microstructurally, word choice and sentence structure build a narrative of struggle and implicit criticism of the system. At the mesostructural level, local MATAMAROS.COM strategic media frame this issue as an urgent social issue, including publication during National Education Day 2025 to maximize impact. Macrostructurally, the news reflects structural inequality due to geographical/economic marginalization, reinforces the ideology of "unsung heroes," and highlights the power imbalance. This descriptive qualitative research concludes that the news is a strong linguistic construct, aiming to mobilize public opinion on inequality in access to education, while reflecting the issue of unequal development and the role of actors in social justice